21. REPEATED VITRIFICATION AND WARMING PROCEDURES HAS NO DETRIMENTAL EFFECT ON BLASTOCYST SURVIVAL AND PREGNANCY OUTCOME. (August 2019) - Tan, S.H.; Lee, C.S.S.; Lim, Y.X.; Lim, M.W.; Chan, C.W.
Abstract : Introduction: In recent years, the freeze all strategy has been widely adopted in IVF clinics on both biopsied and non-biopsied blastocysts to increase the overall IVF success rates. In some cases, patients who have had unsuccessful embryo transfers or repeated miscarriages with non- pre-implantation genetic testing for aneuploidy (PGT-A) blastocysts will opt for PGT-A on their remaining vitrified non-biopsied blastocysts. This study is to evaluate the survival rate of blastocysts and clinical outcome of re-vitrified blastocysts after biopsy in Alpha fertility centre. Material and method: Forty-seven (47) patients had their previous vitrified non-PGT-A blastocysts warmed for biopsy between July 2016 and October 2018. A total of 129 blastocysts which were at least fair graded (Gardner, 1999) were biopsied after post-warmed blastocoel re-expansion. Re-vitrification was performed after biopsy using Cryotec Method (Cryotech, Japan). The biopsied cells were analyzed using Next-Generation Sequencing (Life Technologies, USA). Euploid blastocysts were selected for frozen blastocyst transfer and the clinical outcome were assessed. The post-warmed survival rate of the blastocysts were also evaluated and all successful pregnancies were monitored until delivery. Results: The average maternal age was 31.0 (age range: 18-41). All blastocysts survived post-warm with morphologically intact inner cells mass and trophectoderm cells (100% survival rate) in both vitrified-warmed cycles. Of the 129 blastocysts biopsied, 63.5% (82/129) blastocysts were euploid, 28.6% (37/129) were aneuploid and 7.7% (10/129) were mosaic. Forty one (41) patients had at least one euploid blastocyst while 6 patients had all aneuploid blastocysts. Up till today, 20 of the 41 patients had undergone frozen blastocyst transfer: 18 patients had single blastocyst transfer; 2 had double blastocysts transfer. The clinical pregnancy rate was 55% (11/20) with an implantation rate of 50.0% (11/22). At the time of writing, 6 healthy babies were delivered while 2 pregnancies resulted in miscarriages at 7+1 weeks and 6+4 weeks respectively. There are 3 ongoing pregnancies at 38+1 weeks, 36+2 weeks and 28+1 weeks of gestation respectively. Conclusions: In our experience, repeated vitrification and warming procedures does not affect the viability of the blastocysts, which are capable of progressing to successful pregnancies and healthy live births. Integrating blastocysts re-vitrification into an IVF treatment allows patients who have supernumerary non-biopsied vitrified blastocysts to be warmed, biopsied and re-vitrified without affecting the viability of the blastocysts and their clinical outcomes.